Reading habits and interests of selected Rizal High School students - Ramos, Guizzelle S.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study is about the reading habits and interest on fiction books of selected Rizal High School (Main) students. It aims to know if there are any similarities in the interests of first year to fourth year students, or lack thereof. It also want to find out the factors that affect the reading habits and interest of the students. With this, suggestions and recommendation were made to improve the collection and services on the fiction books of the school.
An ethnographic study was conducted from March 14 to March 25, 2011 at the Rizal High School (Main) Library. Eight students, two from each year level were randomly chosen by the school to participate in the study. The students agreed to participate once the processes and objectives of the study were explained. Each was given journals for the documentation of their reading habits and interests.
The library's fiction collection and a few books brought by the researcher were used as the basis for the fiction books used by the respondents as reference to gauge the reading interests of the respondents.
Several conclusions were made after the journals and interviews of the respondents and the researcher were transcribed and analyzed. Based on the study, most of the high school students have a reading habit; all year levels are interested in action, fantasy and adventure fiction books; the number of fiction books in the library does not contribute to the reading habits and interests of the students because they only borrow books to produce book reports for the Home Reading Program; and the factors that affect their reading habits and interests on fiction books are the students' free time, parents and family, friends, school administration, physical condition and accessibility of the books, popularity of the books, the library environment, the classroom environment and the students' personal reading interests.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Books and reading -- Philippines -- Pasig City; High school students -- Philippines -- Pasig City